Applications of Babalola q-convolution operator on subclass of analytic functions - Timilehin Gideon Shaba; Saravanan Gunasekar; Afis Saliu; Fairouz Tchier; Baskaran Sudharsanan (Journal of Inequalities and Applications)
Abstract In this study, we present a specific type of analytic functions called B γ ( q ) $\mathfrak{B}_{γ}(q)$ , characterized by the Babalola q-convolution operator. We examine the characteristics of this category and set the limits for the initial four coefficients. In addition, we establish the limits for the Toeplitz determinants of second and third order for the functions within this category. Our discoveries offer fresh perspectives on the behavior of these functions and aid in comprehending their structural characteristics.